A meta‐analysis of combining ability effects in wheat for agronomic traits and drought adaptation: Implications for optimizing biomass allocation. Issue 1 (23rd November 2021) - Shamuyarira, Kwame W.; Shimelis, Hussein; Mathew, Isack; Zengeni, Rebecca; Chaplot, Vincent
Abstract: Combining ability effects for yield related traits can serve as selection criteria to pursue breeding for optimal biomass allocation in wheat ( Triticum aestivum ). The objective of this paper is to provide information based on a retrospective quantitative genetic analysis on combining ability studies of wheat for yield and yield‐related traits to predict potential genetic gains achievable in improving biomass allocation for drought tolerance and soil carbon storage. The study compares data on the general combining ability and specific combining ability effects of wheat for yield and related traits under optimum and drought stressed conditions from 40 studies around the world. Days to heading (DTH), plant height (PH), number of tillers per plant (TN), kernels per spike (KPS), 1, 000‐kernel weight (TKW), shoot biomass (SB), and grain yield (GY) exhibited wide variation for general combining ability (GCA) and specific combining ability effects. Progeny performance increased by 14.30 and 4.04% for SB and GY, respectively, compared with parental values under optimum water conditions. Number of tillers and SB exhibited positive associations with GY (.45 ≤ r ≤ .85, p  < .05) under both water conditions. Meta effect sizes for drought stress were negative. The highest meta‐effect sizes were calculated for DTH (−4.5) followed by SB (−2.0), whereas KPS (−1.25) had the lowest. The genetic gains for PH, SB, and other yield components showed that divergent crosses involving complementary parents could enhance biomass allocation patterns in wheat. This could be used as a basis for improving biomass allocation to roots. Core Ideas: There is sufficient genetic variation in wheat genotypes for manipulating biomass allocation. The number of kernels per spike is stable under varying moisture conditions. Shoot biomass and grain yield expression are severely confounded by drought. Aboveground traits are important for indirect selection of root traits.